ExoMol line lists – XLI. High-temperature molecular line lists for the alkali metal hydroxides KOH and NaOH. Issue 1 (4th January 2021) - Owens, A; Tennyson, J; Yurchenko, S N
ABSTRACT: Potassium hydroxide (KOH) and sodium hydroxide (NaOH) are expected to occur in the atmospheres of hot rocky super-Earth exoplanets but a lack of spectroscopic data is hampering their potential detection. Using robust first-principles methodologies, comprehensive molecular line lists for KOH and NaOH that are applicable for temperatures up to T = 3500 K are presented. The KOH OYT4 line list covers the 0–6000 cm −1 (wavelengths λ > 1.67 µm) range and comprises 38 billion transitions between 7.3 million energy levels with rotational excitation up to J = 255. The NaOH OYT5 line list covers the 0–9000 cm −1 (wavelengths λ > 1.11 µm) range and contains almost 50 billion lines involving 7.9 million molecular states with rotational excitation up to J = 206. The OYT4 and OYT5 line lists are available from the ExoMol database at www.exomol.com and should greatly aid the study of hot rocky exoplanets.